Comparative Analysis of CPM, PDM and PERT Methods in Ship Repair Scheduling Planning KN. RB 309 Ternate 01 - Oktafiana, Laily Okta; Baroroh, Intan (Universitas Jember, 2022)
A ship that is still carrying out sailing activities must always be in a state that is in accordance with the classification and statutory. Maintenance or repair is needed for the ship in order to stay in good condition and fit to sail. In a ship repair project, there are several important aspects that need to be considered in order to complete project activities quickly and precisely. PT. XYZ has carried out ship repair activities, but the repair activities have been delayed due to weather factors, and the late procurement of spare parts. This research was conducted by analyzing the three models of scheduling fiberglass ship repair projects using Microsoft excel and using the CPM (Critical Path Method), PDM (Precedence Diagram Method) and PERT (Project Evaluation and Review Technique) methods. Results from the CPM method on 48-day A scheduling, 33-day B scheduling, and 21-day C scheduling. Pdm method results scheduling A 48 days, scheduling B 33 days, and scheduling C 21 days. In the PERT method the project can be completed in 48 days which is 48.67%, scheduling B 34 days 5 hours 21 minutes with the possibility of a KN ship repair project. RB 309 Ternate 01 can be completed in 48 days i.e. 99.35% and scheduling C 22 days 5 hours 21 minutes with the possibility of a KN ship repair project. RB 309 Ternate 01 can be completed in 48 days which is 99.99%.